Proposing the Establishment of the Information and Knowledge Management Organization - Maziar Amirhosseini; Ebrahim Emrani (Iranian Journal of Information Processing & Management)
Non-compliance of the relevant laws of Iran in establishing an educational, research and fraternity union or organization which can be appropriated to the jobs and professions of information science and knowledge studies, as well as the lack of related laws in this case, has been taken into account for more than 50 years. This problem has faced to a new opportunity. The vision of the extraordinary opportunity recognizes in various aspects which are the experiences of pioneer librarians in the establishment of the fraternity union, the development of new careers in the field of information science and knowledge studies, the formation of broad technical, professional and occupational domains based on Information, knowledge and communication technology, the impact of information processing and exchange in people's daily lives, the job market development related to information science and knowledge studies and finally, the mechanism of the establishment of fraternity union and specialized authorities in the fields of engineering and science medical sciences. In this way, relying on the experiences of the initiators, the current condition of the jobs related to information sciences and the formation of new mechanisms in developing fraternity unions, it is possible to formulate and propose legal bills to guarantee fraternity union support. The proposed legal bills should comprise of the scope, role, goals and tasks of the related jobs and professions in the field of information science and knowledge studies. This article attempts to propose the establishment of Information and Knowledge Management Organization for the sake of the creation of the job and profession discipline in achieving professional educational, research and fraternity union goals through discussing the aforementioned cases.